2013
DOI: 10.1039/c3cc40799c
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence generation and elimination: a lesson from glutaraldehyde

Abstract: Glutaraldehyde causes especially high autofluorescence. It reacted with proteins and peptides to generate visible to near-IR emitters. A model indicated that ethylenediamine and a secondary amine in the molecule were key components for the formation of emissive species. The mechanism enables us to control the generation and elimination of autofluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 23 publications
6
67
0
Order By: Relevance
“…21 It has been shown that auto-fluorescence occurs from the chemical treatment of APTES and glutaraldehyde. 22 In our case, we were able to confirm the phenomenon was specific to glutaraldehyde and APTES ( Fig. SI 1a), and use it to show that it only occurs on PDMS in the presence of these chemicals ( Fig.…”
Section: Resultssupporting
confidence: 58%
“…21 It has been shown that auto-fluorescence occurs from the chemical treatment of APTES and glutaraldehyde. 22 In our case, we were able to confirm the phenomenon was specific to glutaraldehyde and APTES ( Fig. SI 1a), and use it to show that it only occurs on PDMS in the presence of these chemicals ( Fig.…”
Section: Resultssupporting
confidence: 58%
“…It is well known that glutaraldehyde, the most used fixative in EM, should be avoided when fluorescence imaging needs to be performed. Glutaraldehyde-fixed samples, indeed, exhibit high levels of autofluorescence when exposed to near ultraviolet light, which decreases the image contrast when other fluorescence signal is detected [2,6,7]. Conversely, formaldehyde is a much less efficient fixative and is not able, when used alone, to guarantee a satisfactory ultrastructure conservation for EM analysis [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…17). 8 Complete, high-fidelity expansion in tissue required a lower MA-NHS concentration than in cultured cells (1 mM for 60 min), presumably due to physical differences in the specimens. We therefore advise validation (through correlative imaging pre- and post-expansion) and possible optimization of these procedures or their variations before applying them to uncharacterized specimens which may have different properties.…”
mentioning
confidence: 99%